2004
DOI: 10.1242/jeb.00858
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation by cadmium of myohemerythrin-like cells in the gut of the annelidNereis diversicolor

Abstract: Trace metals, whether essential such as Cu and Zn or nonessential such as Cd, are taken up by aquatic invertebrates from both food and solutions. After ingestion, the metal is transported around the body, perhaps to be accumulated in particular target organs or even to be excreted (Rainbow, 1998). In most invertebrates, body concentrations of the non-essential metal Cd do not appear to be regulated (Rainbow, 1985;Amiard et al., 1987;Rainbow, 1998). Metal toxicity is often postulated to arise from reactions occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…These two metals were found to be responsible for different types of chromosomal aberrations and lower mitotic index in the fish [52]. Demuynck added that cadmium-binding protein level in the cells of intestine was increased after exposure to Cd, so it appears that this protein will be synthesized as a response to Cd over exposure [52]. Abdelhamid and El-Ayouty, [11] mentioned that the muscles protein content was decreased while that of fat and Pb contents in the fish muscles were increased in proportion to the pollution levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These two metals were found to be responsible for different types of chromosomal aberrations and lower mitotic index in the fish [52]. Demuynck added that cadmium-binding protein level in the cells of intestine was increased after exposure to Cd, so it appears that this protein will be synthesized as a response to Cd over exposure [52]. Abdelhamid and El-Ayouty, [11] mentioned that the muscles protein content was decreased while that of fat and Pb contents in the fish muscles were increased in proportion to the pollution levels.…”
Section: Discussionmentioning
confidence: 99%
“…In the same line Salem, concluded that Cd and Pb negatively affected fish body gain, protein efficiency ratio, chemical composition and muscles area [3]. These two metals were found to be responsible for different types of chromosomal aberrations and lower mitotic index in the fish [52]. Demuynck added that cadmium-binding protein level in the cells of intestine was increased after exposure to Cd, so it appears that this protein will be synthesized as a response to Cd over exposure [52].…”
Section: Discussionmentioning
confidence: 99%
“…It is not clear why N. virens larvae are less tolerant to copper than other species and that the nectochaete stage is much less tolerant than an adult. Polychaetes can excrete, sequester or detoxify significant concentrations of heavy metals using a number of mechanisms including binding metals to metallothioneins and myrohemythrins (Amiard et al, 2006;Demuynck et al, 2007). Differences among species in the efficacy of these mechanisms and that the larval stages may not have fully functioning systems may be responsible for the differences observed.…”
Section: Lc 50 Metal Tests For Nectochaete Larvaementioning
confidence: 99%
“…Troponin I is a part of the troponin complex, which has four binding sites for Ca2+ and Mg2+ and binds actin in thin myofilaments during muscle contraction, is present in the transversely and obliquely striated muscles of E. fetida (Royuela et al, 1996). The involvement of hemerythrins in metal detoxification is controversial (Demuynck et al, 2004) but they have been proposed to play a relevant role in Cd binding in the earthworm Allobophora caliginosa (Nejmeddine et al, 1997). Erythrocruorin is a cooperative oxygen-transporting protein that exists in free solution in blood of E. fetida (Pionetti and Pouyet, 1980).…”
Section: Mechanistic Identification Of Toxicosismentioning
confidence: 99%